Optimal topology for additive manufacture: A method for enabling additive manufacture of support-free optimal structures - Leary, Martin; Merli, Luigi; Torti, Federico; Mazur, Maciej; Brandt, Milan (Materials in engineering, 2014)
[Display omitted] •Topology optimisation is often incompatible with traditional manufacturing methods.•Additive manufacture is more compatible with topologically optimal geometries.•A novel method enables support-free additive manufacture of optimal geometry.•The automated method provides robust design guidance not otherwise available.•Manufacturing time is significantly reduced while avoiding material contamination. Topology optimisation enables profound insight into the optimal material distribution for a given structural objective, applied loading and boundary conditions. The topologically optimal geometry is often geometrically complex and incompatible with traditional manufacturing methods. Additive manufacture can accommodate significantly more complex geometries than traditional manufacture; however, it is necessary that specific design rules be satisfied to ensure manufacturability. Based on identified design for additive manufacture rules, a novel method is proposed that modifies the theoretically optimal topology as required to ensure manufacturability without requiring additional support material. By assessing the manufacturing time and component mass associated with feasible orientations of the proposed geometry, an optimal orientation can be identified. A case study is presented to demonstrate the usefulness of the proposed method.